Do Japanese candlesticks help solve the trader’s dilemma? - Detollenaere, Benoit; Mazza, Paolo (Journal of Banking & Finance, 2014)
In this paper, we investigate whether Japanese candlesticks can help traders to find the best trade-off between market timing and market impact costs. Based on fixed-effect panel regressions on a sample of 81 European stocks, we show that implicit transaction costs are better characterized by using specific Japanese candlesticks patterns. Although market timing costs are not lower when Hammer-like and Doji configurations occur, market impact costs are significantly lower when and after a Doji structure occurs. We further check the potential gains through order submission simulations and find that submission strategies based on the occurrence of Doji result in significantly lower market impact cost than random submission strategies. These findings are of great interest for investors who look for occasional liquidity pools to execute their orders inexpensively such as institutional traders or hedgers.